Mecanisme ale excluziunii de la serviciile de sănătate, cu accent pe problematica romilor - Bleahu, Ana (Calitatea Vieții, 2006)
The reform process, the under-financing and low social control of the health system in Romania limitate the acces of the people to the health services, especialy the acces of the poorest people, roma and non-roma. The inconsistency of the politics regarding the reform of health system creates some mechanisms of exclusion of the population. Thise article is an evaluation of some important mechanisms of exclusion (emphasizing the roma exclusion). The findings of the research are the results of an empiric research in 35 communities with roma, from five counties: Călăraşi, Tulcea, Galaţi, Giurgiu and Bucureşti, in Romania.